Specificity of Procedure Volume and In-hospital Mortality Association - Allareddy, Veerajalandhar (2007)
OBJECTIVE: Several studies have examined the association between procedure-specific volume and in-hospital mortality and concluded that high-volume hospitals have lower mortality rates when compared with low-volume hospitals. There is a paucity of studies examining the association between unrelated procedure volume and in-hospital mortality. The objective of our study is to examine the procedure-specific volume–outcome association as well as unrelated procedure volume–outcome association for 5 procedures: coronary artery bypass graft (CABG), percutaneous coronary interventions (PCI), elective abdominal aortic aneurysm repair (AAA), pancreatectomy (PAN), and esophagectomy (ESO). METHODS: Nationwide Inpatient Sample for years 2000 through 2003 was used. All discharges with primary procedure codes for CABG, PCI, AAA, PAN, and ESO were selected. The average number of procedures performed by the hospitals per year during the study period was computed, and hospitals were categorized as having met or not met the Leapfrog Group-recommended volume thresholds. Procedure specific and unrelated procedure volume–in-hospital mortality association was examined by using multivariable logistic regression analysis. Procedure volume–in-hospital mortality association was adjusted for patient and hospital characteristics. RESULTS: For all 5 procedures, hospitals that did not meet Leapfrog Group volume thresholds were associated with significantly higher odds for in-hospital mortality when compared with hospitals that met Leapfrog Group volume thresholds (P < 0.05). Hospital volume levels for PAN or ESO did not influence outcomes following CABG, PCI, and AAA. Similarly, hospital volumes for CABG, PCI, and AAA did not influence the outcomes for PAN or ESO. CONCLUSIONS: Hospital volume–in-hospital mortality association appears largely to be specific to the procedure being studied.